Effects of Arctic commercial shipping on environments and communities : context, governance, priorities - Huntington, Henry P.; Olsen, Julia; Zdor, Eduard; Zagorskiy, Andrey; Shin, Hyoung Chul; Romanenko, Olga; Kaltenborn, Bjørn Petter; Dawson, Jackie; Davies, Jeremy; Abou-Abbsi, Erin (Transportation Research Part D: Transport and Environment, 2023)
Increasing shipping traffic in the Arctic Ocean creates an emerging need to understand the consequences of maritime operations on the Arctic environment and coastal Indigenous and non-Indigenous communities, as well as potential governance responses. To address this need, we examine recent shipping trends and assess their impact on Arctic environments and communities. Our arguments are novel, and are built around contemporary empirical investigations and published scientific studies, reports, and government documents. The paper concludes that the environmental and community impacts vary across the Arctic and that greater international coordination is needed to learn from experience, to share assets and capacities, and to guide responsible and sustainable development of Arctic shipping. Given the possibility for opening of the Transpolar Sea Route within the coming decades, further proactive steps, such as developing a governance framework, could help Arctic shipping avoid rather than attempt to correct problems. Shipping Arctic routes Indigenous peoples Local communities Social and environmental concerns Risks publishedVersion